Aged and induced-premature ovarian failure mouse models affect diestrus profile and ovarian features - Bacelar, Ana Carolina Zucon [UNESP]; Momesso, Nataira Regina [UNESP]; Pederro, Felipe Haddad Martim [UNESP]; Gonçalves, Alaíde [UNESP]; Ervolino, Edilson [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Biguetti, Claudia Cristina; Matsumoto, Mariza Akemi [UNESP] (Public Library of Science (PLoS), 2023)
Sex hormones exert a wide influence on several systems of the human body, especially in women, who undergo intense changes in the trans and postmenopausal periods. Different experimental models are used to mimic these conditions; however, the impact on hormonal profile may be different. This study aimed to analyze and compare vaginal cytology of different post-estropausal mice models, along with their microscopical ovarian features. Forty-six C57BL/6J female mice with the ages of 4, 6 and 18 months at the beginning of the experiment, weighing about 25–28 grams, constituted five groups: NC–(negative control) animals with no treatment, OVX-SHAM—sham ovariectomized, OVX–ovariectomized, VCD–medicated with 160 mg/kg/day of 4-vinylcyclohexene diepoxide via IP for 20 consecutive days, and Aged–senescent mice under physiological estropause. Euthanasia was performed at different periods for the removal of the ovaries, and after diestrus was confirmed by vaginal cytology for 10 consecutive days. For daily vaginal cytology, morphological and histomorphometric microscopic analyzes were performed. Aged mice presented significant increased neutrophils when compared to VCD group, as well as increased cornified epithelial cells when compared to OVX mice, and also increased nucleated epithelial cells when compared to VCD and OVX. NC and OVX-SHAM ovaries presented innumerous follicles at different stages of development, while VCD showed marked follicular atresia, depleted of primordial or developing follicles and a predominance of interstitial cells. The ovaries of aged mice were predominantly constituted by corpus luteum degenerated into corpus albicans, with rare antral follicles. All analyzed models led to different permanent diestrus profiles caused by each model, as indicated by ovarian features. This should be carefully considered when choosing a post-estropausal experimental model, in order to better correlate this challenging phase of female’s life with physiological/pathological conditions.